Effects of various solar spectra on photovoltaic cell efficiency and photonic hydrogen production. (25th May 2016) - Bicer, Yusuf; Dincer, Ibrahim; Zamfirescu, Calin
Abstract: In this study, an experimental setup is built to investigate the effects of different solar spectra on the PV (photovoltaic) cell efficiency and hence on photonic hydrogen production. A solar simulator is used as an artificial light source, and a spectrometer, an irradiance meter and temperature sensors are utilized for experimental measurements. In addition, potential losses, such as transmittance and reflectance within the system are determined, and the effects of different type of optic filters on solar spectra and the system are investigated and comparatively assessed. The results of this study show that there is an important efficiency decrease when a reflecting mirror for solar simulator is used, and that lower wavelength solar spectrum brings higher PV cell efficiency and hence hydrogen production. Furthermore, solar spectra can be divided for multiple subsystems to efficiently utilize solar energy. Highlights: An experimental unit is built to study the effect of various solar spectra on the PV cell efficiency and hydrogen production. The losses within the system are quantitatively determined. The effects of different type of optic filters on solar spectra and the system performance are investigated and comparatively assessed. Solar spectra can be divided in order to efficiently utilize solar energy by multiple subsystems.